Droop-based active voltage regulation control and robust stability analysis for VSCs in the large-scale RES-integrated power system - Zhao, Zhengkui; Su, Xiaoling; Yang, Jun; Zhou, Peng; Chen, Hui; Lu, Guoqiang (Frontiers in Energy Research, 2022)
New features like high penetration level, low inertia, and weak damping are decreasing voltage support capacity in the power system as it sees large-scale renewable energy source (RES) integration continuously. The reasonable solution to this challenge is developing an additional active voltage regulation function for voltage source converters (VSCs). This study proposes a droop-based active voltage control strategy for VSCs in large-scale RES-integrated power systems to make VSCs continue to operate and regulate the voltage at the point of common coupling (PCC) during a fault without causing overcurrent. In order to meet the requirements of RESs and grid code, all control boundary conditions are designed based on practical engineering data. Meanwhile, plant uncertainty and parameter disturbance are introduced into a robust stability margin analysis model based on the component connection method (CCM) and structured singular value (SSV) to improve the engineering application prospect. The effectiveness and feasibility of this control strategy are proved by logical deduction and practical simulation based on a generalized small-signal model.